KARAKTERISASI SIFAT FISIKOKIMIA PATI UBI JALAR ORANYE (Ipomoea batatas, L.) SERTA PENGGUNAANNYA SEBAGAI KOMPOSIT EDIBLE FILM DENGAN PENAMBAHAN WHEY PROTEIN CONCENTRATE - , JAYANTI TOMO PULUNGSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Packaging is one very important factor in food products. One package that can be eaten along with the packaged product is edible film. The starch of orange sweet potato (Ipomoea batatas, L.) potentially could be used for the manufacture of edible film because the amylose content is good and quite high at 27.71%. High amylose content in the starch will make the film becomes more compact (rigid) but has a fragile nature. The purpose of this study was to determine the physical and mechanical characteristics of edible films based on potato starch orange, glycerol and whey protein concentrate. Edible films made by variation of starch 1,00%, 1,50% and 2,00% (w / v), with a concentration of 30% glycerol (w / w) as plasticizer and whey protein concentrate 2% (w / w). The results showed that the orange sweet potato starch is a polysaccharide starch based spectrum similarity with tapioca starch (commercial). Of reducing sugar test results demonstrated that orange sweet potato starch polysaccharides starch included in the class with a brick red precipitate formation. Increasing the concentration of orange sweet potato starch increases the thickness, and tensile strength, but decrease elongation, water vapour permeability and solubility. At a concentration of orange sweet potato starch 1:00% (w / v), the edible film having a thickness of 0.041 mm, tensile strength of 1.47 MPa, the solubility of 10:24%, amounting to 70.83% elongation, and water vapor permeability of 18.04 grams. mm / mÂ². jam.Kpa.